The Influence of Ideology on Innovation as Manifesting Imagination: The Case of Tescreal and AGI - Hüsig, Stefan; Bucher, Julien (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
In this paper, we introduce an extended version of the concept of innovation as manifesting imagination. In the original concept, imagination has a key role in the preparation, diffusion and success of innovations. Now, we are integrating ideology and illustrating how it acts as a filter: Ideology not only defines what is desirable and what is not, as a complexity-reducing filter it also enables the argumentative reduction of future expectations by focusing on a specific narrative. We propose that the preferable futures that key entities like imaginators recognize, factor in and push are not purely economic in nature but driven by a rather rigid system of beliefs, imaginations, ideals and expectations, an ideology. While research has pointed to the role of institutions as well as the role of internal dynamics in shaping (organizational) behaviors, the role of ideology has been relatively neglected. Presenting the case of TESCREAL and AGI we are shifting the focus from media and the role of social entities to shared systems of believe, the combination of imaginations and ideals. Finally, implications for the formulation of alternative tech visions and strategies are discussed, especially with regards to sustainable development.